2019
DOI: 10.1016/j.rmed.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

VEGF and FGF-2: Promising targets for the treatment of respiratory disorders

Abstract: The endothelial cells play a crucial role in the progression of angiogenesis, which causes cell re-modulation, proliferation, adhesion, migration, invasion and survival. Angiogenic factors like cytokines, cell adhesion molecules, growth factors, vasoactive peptides, proteolytic enzymes (metalloproteinases) and plasminogen activators bind to their receptors on endothelial cells and activate the signal transduction pathways like epidermal growth factor receptor (EGFR phosphatidylinositol 3-kinase and (PI3K)/AKT/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 123 publications
(97 reference statements)
2
96
0
Order By: Relevance
“…Previous studies indicated that hypoxia could upregulate the HIF pathway and might subsequently initiate a pathological process or protective biofunction in cartilage (Bouaziz et al, 2016a;Laddha and Kulkarni, 2019). Indeed, the HIF-1 pathway was previously shown to play a vital role in the maintenance of chondrocyte homeostasis and chondrogenic capacity (Dunwoodie, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that hypoxia could upregulate the HIF pathway and might subsequently initiate a pathological process or protective biofunction in cartilage (Bouaziz et al, 2016a;Laddha and Kulkarni, 2019). Indeed, the HIF-1 pathway was previously shown to play a vital role in the maintenance of chondrocyte homeostasis and chondrogenic capacity (Dunwoodie, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…330 Considering that FGF2 acts as an angiogenic mediator involved in various lung disorders such as COPD, pulmonary fibrosis, pulmonary hypertension, asthma, and lung cancer, FGF2 could also be an crucial target for the treatment of these lung disorders. 331 FGF7 stimulates proliferation of lung epithelial cells and has been considered as a potential therapy for lung injury. 332 FGF9 is a strong candidate contributing to the progression of IPF, which makes it a potential target for the therapies of IPF.…”
Section: Expressions Of Fgf Ligands and Receptors In The Lungmentioning
confidence: 99%
“…This study also verified the angiogenic role of exosomesdelivered miR-23a in molecular levels, as our data shown that VEGF expression was markedly increased, while TSP-1 expression was reduced by GC cell-derived exosomal miR-23a. VEGF, one of the powerful activators of angiogenesis, stimulates endothelial cell migration and proliferation abilities in existing vessels, thereby enhancing the generation and stabilization of new blood vessels (41,42). TSP-1 is a multidomain glycoprotein participated in intercellular and cell to matrix interactions, and particularly related to angiogenesis and tumorigenesis (43).…”
Section: Discussionmentioning
confidence: 99%